Revisiting the corruption of the New Testament : manuscript, patristic, and apocryphal evidence - Wallace, Daniel B. (2011)
How much did the theological arguments of the church affect the copying of the New Testament text? Focusing on issues of textual criticism, this inaugural volume of the Text and canon of the New Testament series offers some answers to that question and responds to some of Bart Ehrman's views about the transmission of the New Testament text. The book begins with the full transcription of Wallace's presentation at the Fourth Annual Greer-Heard Forum, in which he and Bart Ehrman debated over the reliability of the New Testament manuscripts. Adam Messer looks at the patristic evidence of "nor the Son" in Matthew 24:36 in a quest to determine whether the excision of these words was influenced by orthodox Fathers. Philip Miller wrestles with whether the "least orthodox reading" should be a valid principle for determining the autographic text. Matthew Morgan focuses attention on the only two Greek manuscripts that have a potentially Sabellian reading in John 1:1c. Timothy Ricchuiti tackles the textual history of the Gospel of Thomas, examining the Coptic text and the three Greek fragments, using internal evidence in order to determine the earliest stratum of Thomas. Brian Wright thoroughly examines the textual reliability of the passages in which Jesus appears to be called God, concluding that "the textual proof of the designation [Theos] as applied to Jesus in the NT merely confirms what other grounds have already established."
Lost in transmission : how badly did the scribes corrupt the New Testament text? / Daniel B. Wallace -- The least orthodox reading is to be preferred : a new canon for New Testament textual criticism? / Philip M. Miller -- The legacy of a letter : Sabellianism or scribal blunder in John 1.1c? / Matthew P. Morgan -- Patristic theology and recension in Matthew 24.36 : an evaluation of Ehrman's text-critical methodology / Adam G. Messer -- Tracking Thomas : a text-critical look at the transmission of the gospel of Thomas / Tim Ricchuiti -- Jesus as [Theos] : a textual examination / Brian J. Wright.
Papers presented at the Southwestern Regional Evangelical Theological Society conference and later at the at the national Evangelical Theological Society conference held in Providence, Rhode Island in November, 2008
Includes bibliographical references and indexes.
Keywords: Bible. -- Evidences, authority, etc; Bible. -- Canon; Conference papers and proceedings